Oligomerization by co-assembly of β-amyloid and α-synuclein - Kim, Jin Ryoun (Frontiers in Molecular Biosciences, 2023)
Aberrant self-assembly of an intrinsically disordered protein is a pathological hallmark of protein misfolding diseases, such as Alzheimer’s and Parkinson’s diseases (AD and PD, respectively). In AD, the 40-42 amino acid-long extracellular peptide, β-amyloid (Aβ), self-assembles into oligomers, which eventually aggregate into fibrils. A similar self-association of the 140 amino acid-long intracellular protein, α-synuclein (αS), is responsible for the onset of PD pathology. While Aβ and αS are primarily extracellular and intracellular polypeptides, respectively, there is evidence of their colocalization and pathological overlaps of AD and PD. This evidence has raised the likelihood of synergistic, toxic protein-protein interactions between Aβ and αS. This mini review summarizes the findings of studies on Aβ-αS interactions related to enhanced oligomerization via co-assembly, aiming to provide a better understanding of the complex biology behind AD and PD and common pathological mechanisms among the major neurodegenerative diseases.